Maxillary Chronic Osteomyelitis Caused by Domestic Violence: A Diagnostic Challenge - Tamyris Inácio Oliveira; Marina Lara de Carli; Noé Vital Ribeiro Junior; Alessandro Antônio Costa Pereira; Dimitris N. Tatakis; João Adolfo Costa Hanemann (Case Reports in Dentistry)
Maxillary osteomyelitis is a rare condition defined as inflammation of the bone primarily caused by odontogenic bacteria, with trauma being the second leading cause. The present report documents a rare case of maxillary osteomyelitis in a 38-year-old female who was the victim of domestic violence approximately a year prior to presentation. Intraoral examination revealed a lesion appearing as exposed bony sequestrum, with significant destruction of gingiva and alveolar mucosa in the maxillary right quadrant, accompanied by significant pain, local edema, and continued purulence. Teeth numbers 11, 12, 13, 14, and 15 were mobile, not responsive to percussion, and nonvital. Treatment included antibiotic therapy for seven days followed by total enucleation of the necrotic bone tissue and extraction of the involved teeth. Microscopic findings confirmed the clinical diagnosis of chronic suppurative osteomyelitis. Six months postoperatively, the treated area presented complete healing and there was no sign of recurrence of the lesion.